(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2026)
Octavia E. Butler emerges as a foundational figure in American speculative fiction by foregrounding Afro-American experience within dystopian futures. This article argues that Butler’s racial identity as an Afro-American writer decisively shapes the social, ethical, and political imagination of Parable of the Sower and Parable of the Talents. Rather than treating the future as a detached or universal space, Butler constructs dystopian worlds that extend historical patterns of racial inequality, economic dispossession, and institutional violence. Through the protagonist Lauren Olamina and the philosophy of Earthseed, Butler reframes survival as a collective, adaptive, and morally grounded practice rooted in Afro-American historical consciousness. The study situates the Parable novels within Black feminist thought and Afrofuturist discourse to demonstrate how Butler resists dominant narratives of progress and technological salvation. Her fiction insists that the future cannot erase race but must confront its enduring structures. By analysing how Butler integrates race, embodiment, and ethical responsibility into speculative world-building, this article highlights her contribution to reimagining futurity as an ongoing struggle shaped by memory, resilience, and communal care. The article contributes to contemporary literary scholarship by foregrounding Afro-American identity as the generative force of Butler’s dystopian imagination.